(untitled) (Memoria Americana. Cuadernos de Etnohistoria, 2021)
In a context of re-emergence of indigenous communities in Córdoba, Argentina, this paper aims to analyze the hegemonic representations of the Comechingon people in the long duration. For this matter, we identify three historical periods in which we find different dominant conceptions about the indigenous people in general and the Comechingon in particular: the Spanish Conquest, when this ethnonym was imposed as a way of homogenizing the various peoples that inhabited the region; the 19th century, when the new nation-state ruling elite sought the invisibilization of all traces of indigenous people; finally, during the 20th century, when both anthropology and historiography brought back the culture and history of the pre-Hispanic indigenous people but, once again, denied their present and their future.